Price Factor Analysis, Word Of Mouth And Experiential Marketing On Customer Loyalty During The Covid-19 Pandemic (Case Study On The Tebing Tinggi Family Bakery) - Rumiris Siahaan; Suci Etri Jayanti (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2022)
This study aims to determine how the influence of price, word of mouth and experiential marketing on customer loyalty during the Covid-19 pandemic. This study uses a quantitative research type with the help of the IBM SPSS 25.00 application. The results of hypothesis testing using multiple linear regression analysis with three independent variables and one dependent variable show that From Table 4.18 it is known: that tcount (2.865) > t table (1.986), as well as the significance value of 0.005 <0.05, it can be concluded that the first hypothesis is accepted, meaning Price variable (X1) has an effect to the Customer Loyalty variable (Y). From Table 4.18 it can be seen that tcount (4,914) > t table (1.986), as well as the significance value of 0.000 <0.05, it can be concluded that the second hypothesis is accepted, meaningvariable Word of Mouth (X2) has an effect to the Customer Loyalty variable (Y). From Table 4.18 it can be seen that tcount (1,993) > t table (1.986), as well as the significance value of 0.049 <0.05, it can be concluded that the third hypothesis is accepted, meaningvariable Experiential Marketing (X3) take effect to the Customer Loyalty variable (Y).